Examining the Relationship Between Consumer Innovativeness and Trust in Chatbot Applications: A Study on Turkish Banking Sector - Denecli, Sevda; BALABAN, ÖYKÜ EZGİ YILDIZ; Arıbakan, Ceyda Denecli (Istanbul Univ, Fac Communication, 2022)
Life has transformed rapidly with technology taking on a dominant position in our time. The developments in the field of the internet and the point that web technology has reached has created radical changes in the way of life of today's individuals. Businesses also benefit from the opportunities that technology had provided them in how they reach their consumers. Businesses are using these technologies more and more every day to reach consumers who are constantly open to interaction thanks to technological tools. This is especially true in the service sector and e-commerce sites, where the effects of the digital transformation in banking are seen more clearly. Banks have started to use artificial intelligence-based robots in the customer relations process. In the present study, the general development of artificial intelligence-based chatbots was examined and their use in the rapidly digitalizing banking field was discussed. In this context, the approaches of innovative consumers to chatbot applications of banks were evaluated. The research was carried out on 407 people who were reached by convenience sampling method, using a questionnaire as a data collection method. However, since 13 people stated that they do not use internet or mobile banking, the analyzes were carried out on the answers of 394 participants. A correlation analysis was conducted to reveal whether the innovativeness level of consumers is related to their trust in chatbot applications. The research results show that there is no significant relationship between the "competence dimension" (r=0.06; p<0,01) and "benevolence dimension" (r= 0.06; p<0,01) of consumer trust towards chatbot applications and consumer innovativeness; however, study revealed that there is a significant relationship between the "integrity dimension" (r=0.17; p<0,01) of trust and consumer innovativeness.
Keywords: Artificial Intelligence; Chatbot; Digitalization; Innovative Consumer; Consumer Cxperience